2020
DOI: 10.33882/jida.13.25520
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Audio-Visual Aid in Improving Knowledge and Awareness Towards Infant Oral Health Care for Expectant Mothers

Abstract: Aim: The objective of this study was to evaluate the efficacy of a PowerPoint Presentation in Up-grading the knowledge and awareness towards infant oral health care among expectant mothers. Methods: This was a cross sectional survey conducted in various maternity hospitals throughout Jaipur city, India. A 15 minute PowerPoint Presentation based on infant oral health care was presented to a total of 120 expectant mothers. The participants were made to fill a 15-point questionnaire on the same subject before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Parents instead postulated that oral health messages employing audio-visual aids would engage their attention and studies have shown that slideshows and videos are beneficial in improving the oral health awareness of parents. 25 , 26 Parents also deduced that it would be useful if copies of such resources were repeated and reinforced in the community. Exposure of parents to comprehensive and interactive education using audio-visual aid one-time resulted in a reduction in caries incidence and an increase in dental utilisation, however, some attrition in information retention was noted after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Parents instead postulated that oral health messages employing audio-visual aids would engage their attention and studies have shown that slideshows and videos are beneficial in improving the oral health awareness of parents. 25 , 26 Parents also deduced that it would be useful if copies of such resources were repeated and reinforced in the community. Exposure of parents to comprehensive and interactive education using audio-visual aid one-time resulted in a reduction in caries incidence and an increase in dental utilisation, however, some attrition in information retention was noted after 18 months.…”
Section: Discussionmentioning
confidence: 99%